Grading evaluation methods for lacustrine shale oil resources developed by in-situ heating conversion technology - Lin, Senhu; Luo, Xia; Zhao, Zhongying; Hou, Lianhua; Li, Shixiang; Li, Hui; Pang, Zhenglian; Zhang, Lijun (Frontiers in Earth Science, 2025)
In-situ conversion technology is a sustainable and effective method of recovering medium-low maturity shale, which can be produced with oil resources expected to exceed global total proven oil reserves. Nevertheless, criteria and procedures for grading such shale oil resources are lacking. We present a combination of distinct faceis and theoretical economic index (Ie) to grade the in-situ conversion shale oil resources of Chang 7 Member in the Ordos Basin and Nenjiang Formation in the Songliao Basin. This shale oil resource was categorized into four classes: invalid, valid, sweet-spot and core resource. For the shale dominated by type II kerogen (Chang 7), total organic carbon (TOC) values at 6%, 9%, and 12%, hydrocarbon generation potential (S1+S2) values at 15 mg/g, 30 mg/g, and 50 mg/g, and Ie at 2, 3, and 4, respectively, represent the boundary of the four resource grades. For the shale dominated by type Ⅰ kerogen (Nenjiang), TOC values at 4%, 6%, and 8%, S1+S2 values at 19 mg/g, 32 mg/g, 48 mg/g, and Ie at 2, 3, and 4, respectively, represent the boundary of the four resource grades. Our research provides a feasible practical strategy for evaluating and predicting in-situ conversion shale oil resources in lacustrine basins.